Phylogeography of screaming hairy armadillo Chaetophractus vellerosus: Successive disjunctions and extinctions due to cyclical climatic changes in southern South America - Poljak, Sebastián (2018)
Little is known about phylogeography of armadillo species native to southern South America. In this study we describe the phylogeography of the screaming hairy armadillo Chaetophractus vellerosus, discuss previous hypothesis about the origin of its disjunct distribution and propose an alternative one, based on novel information on genetic variability. Variation of partial sequences of mitochondrial DNA Control Region (CR) from 73 individuals from 23 localities were analyzed to carry out a phylogeographic analysis using neutrality tests, mismatch distribution, median-joining (MJ) network and paleontological records. We found 17 polymorphic sites resulting in 15 haplotypes. Two new geographic records that expand known distribution of the species are presented; one of them links the distributions of recently synonimized species C. nationi and C. vellerosus. Screaming hairy armadillo phylogeographic pattern can be addressed as category V of Avise: common widespread linages plus closely related lineages confined to one or a few nearby locales each. The older linages are distributed in the north-central area of the species distribution range in Argentina (i.e. ancestral area of distribution). C. vellerosus seems to be a low vagility species that expanded, and probably is expanding, its distribution range while presents signs of genetic structuring in central areas. To explain the disjunct distribution, a hypothesis of extinction of the species in intermediate areas due to quaternary climatic shift to more humid conditions was proposed. We offer an alternative explanation: long distance colonization, based on null genetic variability, paleontological record and evidence of alternance of cold/arid and temperate/humid climatic periods during the last million years in southern South America.